2021
DOI: 10.3389/fimmu.2021.713132
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional KLRG-1+CD57+ Senescent CD4+ T Cells Infiltrate Tumors and Are Expanded in Peripheral Blood From Breast Cancer Patients

Abstract: Senescent T cells have been described during aging, chronic infections, and cancer; however, a comprehensive study of the phenotype, function, and transcriptional program of this T cell population in breast cancer (BC) patients is missing. Compared to healthy donors (HDs), BC patients exhibit an accumulation of KLRG-1+CD57+ CD4+ and CD8+ T cells in peripheral blood. These T cells infiltrate tumors and tumor-draining lymph nodes. KLRG-1+CD57+ CD4+ and CD8+ T cells from BC patients and HDs exhibit features of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…In this regard, one limitation of our analysis is that it does not dismiss the contribution of CD39 + expression in CD8 + T cells. However, our previous observation that BC tumors exhibit greater proportions of TI-CD4 + than CD8 + T lymphocytes 21 supports the relevance of the contribution of the CD39-expressing CD4 + T cell in overall survival.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this regard, one limitation of our analysis is that it does not dismiss the contribution of CD39 + expression in CD8 + T cells. However, our previous observation that BC tumors exhibit greater proportions of TI-CD4 + than CD8 + T lymphocytes 21 supports the relevance of the contribution of the CD39-expressing CD4 + T cell in overall survival.…”
Section: Discussionsupporting
confidence: 55%
“…TFs (intracellular staining) and intracellular cytokine detection cells were performed following protocols previously described 16, 21 .…”
Section: Methodsmentioning
confidence: 99%
“…In line with previous studies, patients with HGSOC showed elevated frequency of Tsen CD8 + T cells in the peripheral blood compared with age-matched HDs. In patients with breast cancer, the frequency of Tsen CD4 + T cells was also significantly increased ( 27 ). However, in patients with HGSOC, the frequency of Tsen CD4 + T cells in the peripheral blood was comparable to HDs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer patients, killer cell lectin-like receptor G1 (KLRG-1) + CD57 + CD4 + and CD8 + senescent T cells that produce more effector cytokines, granzyme B and perforin accumulate in peripheral blood and in the tumor. The expression of CD4, KLRG-1, and CD57 correlates with increased overall survival for breast cancer patients [139]. Contrary to the beneficial role of KLRG-1 + CD57 + CD4 + senescent Th cells in breast cancer patients, Ye et al showed that tumor-derived γδ T cells induce senescence in CD4 + T cells and also in DCs that were no longer able to process and present tumor antigens to T cells.…”
Section: Senescence Induction In Cells Of the Immune Systemmentioning
confidence: 99%